Fullness of time : ethnohistory selections from the writings of Alan R. Tippett - Tippett, Alan R. (Alan Richard), 1911-1988 (Missiology of Alan R. Tippett series., 2014)
Alan Tippett's publications played a significant role in the development of missiology. The volumes in this series augment his distinguished reputation by bringing to light his many unpublished materials and hard-to-locate printed articles. These books--encompassing theology, anthropology, history, area studies, religion, and ethnohistory-- broaden the contours of the discipline. Tippett believed his writings on ethnohistory were his most original contribution to the discipline of missiology. The wealth of material in Fullness of Time is his best ethnohistory writing--most of which has never been published. Explore the methods and models of this captivating field of study. Realize how documents, oral tradition, and even artifacts can be used to recreate the cultural situation of a prior time. Learn about the South Pacific, Ethiopia, Hawaii, and Australia, both in and through time.